2013
DOI: 10.1523/jneurosci.4286-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Avalanches in the Resting MEG of the Human Brain

Abstract: What constitutes normal cortical dynamics in healthy human subjects is a major question in systems neuroscience. Numerous in vitro and in vivo animal studies have shown that ongoing or resting cortical dynamics are characterized by cascades of activity across many spatial scales, termed neuronal avalanches. In experiment and theory, avalanche dynamics are identified by two measures: (1) a power law in the size distribution of activity cascades with an exponent of −3/2 and (2) a branching parameter of the criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
394
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(437 citation statements)
references
References 49 publications
22
394
1
1
Order By: Relevance
“…Comparison of intracellular and extracellular spike activity demonstrated that during up-state periods, all neurons are depolarized and pyramidal neurons display average firing rates of ∼1 Hz, typical found for resting activity in vivo (24,48). In fact, the spatiotemporal organization of the neuronal population activity during up-states (25,28) is characteristic of neuronal avalanches, the resting state organization identified in vivo in rodents, nonhuman primates (27), and humans (49). We therefore conclude that up-state activity measured in organotypic cultures best matches ongoing resting activity in vivo.…”
Section: Discussionmentioning
confidence: 70%
“…Comparison of intracellular and extracellular spike activity demonstrated that during up-state periods, all neurons are depolarized and pyramidal neurons display average firing rates of ∼1 Hz, typical found for resting activity in vivo (24,48). In fact, the spatiotemporal organization of the neuronal population activity during up-states (25,28) is characteristic of neuronal avalanches, the resting state organization identified in vivo in rodents, nonhuman primates (27), and humans (49). We therefore conclude that up-state activity measured in organotypic cultures best matches ongoing resting activity in vivo.…”
Section: Discussionmentioning
confidence: 70%
“…As a matter of fact, such models have been reported to achieve the best performance -e.g. reproducing empirically-observed resting-state networks (68)-when operating close to the synchronization phase transition point (64,87,88).Within our framework, it is possible to define a protocol to analyze avalanches, resembling very closely the experimental one (7, 8, 11,16,17). Thus, in contrast with other computational models, causal information is not explicitly needed/employed here to determine avalanches -they are determined from raw data-and results can be straightforwardly compared to experimental ones for neuronal avalanches, without conceptual gaps (40).…”
mentioning
confidence: 65%
“…to be organized in a scale-free way, limited only by network size (7). Furthermore, they obey finite-size scaling (8), a trademark of scale invariance (9), and the corresponding exponents are compatible with those of an unbiased branching process (10).Scale-free avalanches of neuronal activity have been consistently reported to occur across neural tissues, preparation types, experimental techniques, scales, and species (11)(12)(13)(14)(15)(16)(17)(18). This has been taken as empirical evidence backing the criticality hypothesis, i.e.…”
mentioning
confidence: 99%
“…Our main motivation is due to the recent observation of neuronal avalanches and their presumed relation to SOC. In a wide range of recent experiments [14][15][16][17][18][19][20][21] , neuronal avalanches have been shown to exhibit power law behavior with mean-field exponents. Whether neural dynamics [22] is dissipative or not is still debated, but their noisy dynamics [23] is a certainty, as the post-synaptic neurons receive more or less than their fair share of the ion distributed by the pre-synaptic neuron in the ionic plasma, which permeates the space between synapses.…”
Section: Introductionmentioning
confidence: 99%